L'État et les écoles privées primaires au Tamil Nadu et à Pondichéry (Inde) : une forme de partenariat - Émilie Ponceaud Goreau (Les éditions de la Maison des sciences de l'Homme, 2021)
This paper presents the multiple recompositions and arrangements that are taking place in the primary education sector in Tamil Nadu and Pondicherry. In the aftermath of independence, Educational policies have evolved under the influence of a popular electorate and a strong regional identity. The challenge is to show how this model is evolving in a neoliberal context, subject to a new world educational order and under pressure from parents, who have been particularly inclined since the 2000s to espouse the codes of the new middle classes without, in most cases, belonging to them. The paper questions the conditions for the emergence and exercise of private non-state actors and also the way in which the State, particularly the regional State, negotiates relations between the public and private sectors through reservations, subsidies and vouchers. Focusing on the effects of national and regional education policies based on research conducted in Tamil Nadu and Pondicherry since 2013, the paper emphasizes on a qualitative material from semi-directive interviews with pre-schooling actors and families, questionnaires and observations, supported by the dual status of the author as a researcher and teacher by profession in France.